The Island - Michael Bay; Ewan McGregor; Scarlett Johansson; Djimon Hounsou; Sean Bean; Steve Buscemi; Duncan, Michael Clarke; Ethan Phillips (USA DreamWorks, 2005)
Lincoln Six-Echo is a resident of a seemingly Utopian but contained facility in the year 2019. Like all of the inhabitants of this carefully controlled environment, Lincoln hopes to be chosen to go to the "The Island" - reportedly the last uncontaminated spot on the planet. But Lincoln soon discovers that everything about his existence is a lie. He and all of the other inhabitants of the facility are actually human clones. Lincoln makes a daring escape with a beautiful fellow resident named Jordan Two-Delta. Relentlessly pursued by the forces of the sinister institute that once housed them, Lincoln and Jordan engage in a race for their lives to literally meet their makers.
Language(s): English Subtitle(s): Turkish
Keywords: Action; Adventure; Sci-Fi